Placing social imaginaries to reconceptualize conservation from a social-ecological perspective: insights from guided visits to a Patagonian national park - Jessica Balling; Christopher B. Anderson (Journal of Environmental Studies and Sciences, 2026)
More inclusive conservation approaches are needed to achieve the dual goals of justice and sustainability. This imperative requires developing new strategies to adapt extant models like conservation-based tourism in protected areas to incorporate more plural perspectives. We studied guided tours in Tierra del Fuego National Park, Argentina to assess how nature and people-nature relationships were (re)produced. Specifically, we used ethnographic methods (participant observations, interviews, document/media analyses) with the bricolage analytical concept of ‘placing social imaginaries’ to evaluate the ways that materialities, practices, meanings, and institutions interact in the visitation experience. We delimited three dynamic areas of tension evident in the data: (i) remoteness - connectivity, (ii) modernity - postmodernity, and (iii) singular nature - plural people-nature relationships. By analyzing how multiple social imaginaries converge and reproduce different people-nature relationships in touristic experiences, we obtained insights into how a ‘natural’ protected area is conceived, valued, and co-constructed as a dynamic social-ecological system in a specific space-time (i.e. place). We argue that being more intentional and reflexive about the ‘placing of social imaginaries’ can foster more inclusive approaches to conservation-based tourism.